Kritik Antroposentrisme Kantian dalam Novel Niṣf Basyar Karya Asma' Muhsin melalui Perspektif Posthumanisme - Ergiansyah, Mochamad Rifki; Yuningsih, Yeni Ratna (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study analyzes the novel Niṣf Basyar (2017) to explore how the text dismantles anthropocentrism, particularly Immanuel Kant's humanist framework, in contemporary Arabic literature. Using a qualitative library-based method, data comprising narratives, dialogues, and character actions were collected through reading and note-taking. The data were first analyzed using Robert Stanton's structuralist approach to map story facts, themes, and literary devices. Subsequently, these elements were examined using Rosi Braidotti and Donna Haraway's critical posthumanist frameworks to trace critiques of Kantian concepts, including the Copernican revolution, moral dignity, and the phenomenon-noumenon boundary. The findings demonstrate that the novel dismantles anthropocentric hierarchies cumulatively. First, non-human agents subvert human sovereignty in distinct ways: Alpha and Beta expose the fragility of human superiority, whereas Sari and Delta invert the Kantian distinction between means and ends through autonomous moral actions. Second, scientific taxonomy is exposed as an instrument of power rather than neutral reason, with affect functioning as an ethical counterpoint to rational and scientific classification. Third, the hybrid protagonist Nisrina embodies an ontological anomaly that defies both human forensic science and alien biological knowledge, thereby collapsing the Kantian boundary between phenomena and noumena. The study concludes that Niṣf Basyar offers an example of posthumanist critique in contemporary Arabic literature, demonstrating that anthropocentrism collapses not through a single narrative event but through the accumulated failure of human rational, epistemological, and biological claims to sovereignty.